Advances in materials technology for fossil power plants : proceedings from the fourth international conference, October 25-28, 2004, Hilton Head Island, South Carolina - Viswanathan, Ramaswamy; Gandy, D, (David); Coleman, K, (Kent) (ASM International, 2006)
Section 1: Plenary papers.- Section 2: Boiler meteriales. - Section 3: Steam turbine meterials. -Section 4: Life management.- Section 5: Weld behavior. -Section 6: Microestructural effects in creep. -Section 7: Appendix. -Section 8: Reference information.